Green synthesis of iron nanoparticles from the baru (Dipteryx alata) endocarp extract for the efficient removal of rhodamine B and caffeine from water through the heterogeneous Fenton process - Reinehr Corrêa, Cassiano Ricardo; de Siqueira, Adriano Buzutti; Matos Lopes, Paulo Renato [UNESP]; Ribeiro Ambrosio, Jéssica Aparecida; Simioni, Andreza Ribeiro; de Vasconcelos, Leonardo Gomes; de Morais, Eduardo Beraldo (IWA Publishing, 2024)
This study presents the first-time synthesis of iron nanoparticles (FeNPs) using an aqueous extract from the baru fruit endocarp (Dipteryx alata). Characterization through scanning electron microscopy and dynamic light scattering revealed spherical shapes with an average diameter of 419.2 nm. Fourier transform infrared spectroscopy identified phytochemicals from the baru fruit extract, acting as both reducing and stabilizing agents. X-ray diffraction confirmed the amorphous nature of the FeNPs. The Fenton-like catalytic efficiency of FeNPs was investigated for degrading rhodamine B (RhB) and caffeine. The impact of crucial parameters such as pH, H2O2 dosage, nanoparticles concentration, and temperature on the degradation process was assessed. At pH 3.0, with 1.0 g L‒1 of FeNPs, 1% H2O2, and 45 °C, RhB and caffeine degradation reached 99.14 and 92.01%, respectively. The catalytic reaction kinetics followed a pseudo-first-order model for caffeine and a pseudo-second-order model for RhB. Phytotoxicity studies on Cucumis sativus confirmed the non-toxic nature of the degraded products of RhB and caffeine. These findings highlight the potential of FeNPs synthesized from the baru endocarp extract as a catalyst for removing organic pollutants, suggesting promising applications in environmental remediation and related fields.
Keywords: Fenton-like catalysis; green chemistry; iron nanoparticles; metallic nanoparticles; plant extract